Analisis Kesalahan Fonologi Membaca Teks Bahasa Arab Pada Siswi Kelas VII MTs Putri Ma’arif Ponorogo - ana, Sri; Muballighin, Kulyatul (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
This study aims to describe the forms of phonological errors, phonological error factors, and solutions to phonological errors in reading Arabic texts in class VII students of MTs Putri Ma'arif Ponorogo. This study uses a qualitative approach with a case study type of research. Methods of data collection is done by using the method of observation, interviews, and documentation. Data analysis was carried out by going through the stages of data reduction, data display, and data verification or drawing conclusions. Data validity test was carried out using the triangulation method. The results of this study indicate that (1) the form of phonological errors in reading Arabic texts is in the form of phoneme changes, phoneme subtraction, and phoneme addition. (2) the factors that cause phonological errors are the background of the students before entering MTs, the lack of interest in learning Arabic, the lack of concentration of students when learning takes place in class, inadequate facilities and infrastructure, and whether or not the students often read the Al-Qur'an at home. (3) the solution given by the teacher to deal with phonological errors is to provide more material to children who are lacking in mastering reading skills, prepare facilities and infrastructure that have not been fulfilled as learning support, provide motivation about the importance of learning Arabic, and emphasize learning on their own at school House.